2021
DOI: 10.1590/1413-81232021264.08562019
|View full text |Cite
|
Sign up to set email alerts
|

Conexão com a natureza e associação com motivos de escolhas alimentares entre profissionais da atenção primária à saúde

Abstract: Resumo A conexão com a natureza pode favorecer o bem-estar e a adoção de práticas alimentares sustentáveis. Profissionais de saúde seriam agentes fundamentais nesta interface, promovendo a saúde ambiental. Estudo transversal com 146 profissionais da atenção primária avaliou a associação entre conexão com a natureza e os motivos para escolhas alimentares consideradas importantes à saúde humana e ambiental. Aplicou-se Escala de Conexão com a Natureza (ECN), contendo 14 itens que medem o quanto a pessoa se sente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Spendrup et al ( 2016) and Baldi et al (2021) showed a positive association between connectedness to nature and willingness to purchase organic products. Finally, Bruno et al (2021) found that people with a higher level of connectedness report consuming more food that they consider "ethical" and "natural". To our knowledge, there is currently no study that mobilizes connectedness to nature as a mediator of the link between attitudes and behaviour regarding sustainable eating.…”
Section: Sustainable Food Consumption: Which Predictors?mentioning
confidence: 97%
“…Spendrup et al ( 2016) and Baldi et al (2021) showed a positive association between connectedness to nature and willingness to purchase organic products. Finally, Bruno et al (2021) found that people with a higher level of connectedness report consuming more food that they consider "ethical" and "natural". To our knowledge, there is currently no study that mobilizes connectedness to nature as a mediator of the link between attitudes and behaviour regarding sustainable eating.…”
Section: Sustainable Food Consumption: Which Predictors?mentioning
confidence: 97%
“…Accordingly, primary healthcare professionals should encourage health practices to enable the applicability of community intervention methods focused on broadening the perception of people affected by environmental issues, as well as on empowering them to improve their environmental and health conditions (Moniz, Daher, Sabóia & Ribeiro, 2020). However, these health professionals are often unprepared to take actions aimed at promoting healthy environments and ecologically sustainable attitudes (Bruno et al, 2021).…”
Section: Introductionmentioning
confidence: 99%